Effect of Quality of Health Services and Facilities on Patient Satisfaction at Mulyoharjo Health Center, Pemalang Regency - Azlya Fahrezi Muhammad; Purwito Soegeng Prasetijono; Andhika Dwi Anggara (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Patients provide critical feedback on healthcare delivery, and satisfaction levels tend to rise when service performance exceeds patient expectations. Research is being conducted at the Mulyoharjo Health Center, Pemalang Regency, to inquire the proceeds of service quality and healthcare facilities on patient satisfaction. Our study employed a quantitative observational draw utilizing a cross-sectional design that involved 100 outpatients selected using purposive sampling. In addition to normality assessments, multiple linear regressions, t-tests, F-tests, coefficient of determination analysis, and TCR evaluations, data were analyzed using a several of statistical techniques. According to the results, both service quality and facility availability contribute significantly and positively to patient satisfaction, on both an individual and collective basis. In contrast, the F-test value reached 200.767, which was significantly higher than the threshold of 3.09 for the F-table, while the t-test results indicated that patient satisfaction was significantly affected by service quality (t-count: 11.200) and facilities (t-count: 4.184), exceeding the critical t-value of 1.660. The TCR method was also used to analyze the quality of service, availability of facilities, and overall patient satisfaction. Service quality and facility accessibility contributed 80.1% of the discrepancy in patient satisfaction, with the remaining 19.9% attributable to other factors not taken into account. In summary, the findings affirm that service quality and facility availability play a crucial role in enhancing patient satisfaction at the Mulyoharjo Health Center.